2015
DOI: 10.1007/s11356-015-5876-6
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial humic substances in Daliao River and its estuary: optical signatures and photoreactivity to UVA light

Abstract: Fluorescent dissolved organic matter (FDOM) components were identified by Parallel Factor Analysis (PARAFAC) in surface water of Daliao River and its estuary with a focus on terrestrial humic substance-(HS)-like FDOM identified under two contrasting hydrological conditions. The hydrological conditions did not have noticeable effect on the spectral features of the terrestrial HS-like FDOM, but did affect the components' intensities and photoreactivity: (1) the intensities of terrestrial HS-like components were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
0
0
Order By: Relevance
“…Tetsuro Kikuchi et al [11] examined the relationship between DOM and trace metals in both natural and sewage water, revealing that dissolved copper and iron concentrations were influenced by DOM concentration and the presence of aromatic DOM. Chen et al [12] investigated the composition of dissolved organic matter in surface waters across various river reaches, elucidating the influence of UV light and hydrological conditions on terrestrial humus content. Moreover, they revealed that DOM exhibits distinct photoresponsive characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Tetsuro Kikuchi et al [11] examined the relationship between DOM and trace metals in both natural and sewage water, revealing that dissolved copper and iron concentrations were influenced by DOM concentration and the presence of aromatic DOM. Chen et al [12] investigated the composition of dissolved organic matter in surface waters across various river reaches, elucidating the influence of UV light and hydrological conditions on terrestrial humus content. Moreover, they revealed that DOM exhibits distinct photoresponsive characteristics.…”
Section: Introductionmentioning
confidence: 99%